2018
DOI: 10.1007/s10404-018-2069-x
|View full text |Cite
|
Sign up to set email alerts
|

The study of atmospheric ice-nucleating particles via microfluidically generated droplets

Abstract: Ice-nucleating particles (INPs) play a significant role in the climate and hydrological cycle by triggering ice formation in supercooled clouds, thereby causing precipitation and affecting cloud lifetimes and their radiative properties. However, despite their importance, INP often comprise only 1 in 103–106 ambient particles, making it difficult to ascertain and predict their type, source, and concentration. The typical techniques for quantifying INP concentrations tend to be highly labour-intensive, suffer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 216 publications
(324 reference statements)
2
57
0
Order By: Relevance
“…In contrast bulk methods such as drop-freezing assays (Hill et al, 2014;Stopelli et al, 2014;Vali, 1971), differential scanning calorimetry (Kaufmann et al, 2016;Pinti et al, 2012) and microfluidic devices (Reicher et al, 2018;Riechers et al, 2013;Stan et al, 2009;Tarn et al, 2018) immerse the samples in water and can be used to detect lower atmospheric INP concentrations. The majority of atmospheric INP concentrations at temperatures above −15 • C have been quantified using drop-freezing assays.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast bulk methods such as drop-freezing assays (Hill et al, 2014;Stopelli et al, 2014;Vali, 1971), differential scanning calorimetry (Kaufmann et al, 2016;Pinti et al, 2012) and microfluidic devices (Reicher et al, 2018;Riechers et al, 2013;Stan et al, 2009;Tarn et al, 2018) immerse the samples in water and can be used to detect lower atmospheric INP concentrations. The majority of atmospheric INP concentrations at temperatures above −15 • C have been quantified using drop-freezing assays.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of atmospheric INP concentrations at temperatures above −15 • C have been quantified using drop-freezing assays. To retrieve the concentrations of INP from such bulk suspensions, Vali (1971Vali ( , 2019 showed that by dividing a sample into several aliquots, it is possible to calculate the number of INPs present in the sample as a function of temperature. The probability for more than one INP in an aliquot that freezes at the same temperature can be predicted using Poisson's law (Vali, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations